Environmental Science For Dummies - Spooner, Alecia M. (For Dummies, 2023)
Ace your environmental science class and get smart about the environment Environmental Science For Dummies is a straightforward guide to the interrelationships of the natural world and the role that humans play in the environment. This book tracks to a typical introductory environmental science curriculum at the college level--and is great as a supplement or study guide for AP Environmental Science, too. Uncover fascinating facts about the earth's natural resources and the problems that arise when resources like air, water, and soil are contaminated by pollutants. If you're in need of extra help for a class, considering a career in environmental science, or simply care about our planet and want to learn more about helping the environment, this friendly Dummies resource is a great place to start. The key concepts of environmental science, clearly explained All about the changing climate, including new understanding of methane release in the arctic Earth's natural resources and the importance of protecting them A new chapter on environmental justice, where issues of poverty and sustainability intersect A solid foundation in environmental science is essential for anyone looking for a career in the field--and is important knowledge for all of us as we work together to build a sustainable future.